The Mediating Role of Affective Commitment in The Relationship Between Self-Efficacy and Employee Performance in Hotels in Sorong City - Reijeng Tabara; Rohsita Amalyah Rasyid; Angelina Kolim Srer (Yayasan Jompa Research and Development, 2026)
This study examines the effect of self-efficacy on hotel employee performance with affective commitment as a mediating variable, based on Social Cognitive Theory and Social Exchange Theory. Using a quantitative-explanatory survey, data were collected from 172 full-time employees at three- and four-star hotels in Sorong City, Southwest Papua. Data were analyzed using PLS-SEM with SmartPLS 4.0. The results of the structural model analysis revealed that self-efficacy has a positive and significant effect on affective commitment and employee performance. Affective commitment has a positive and significant effect on performance and partially and significantly mediates the relationship between the two. This model explains 83.9% of the variance in employee performance, indicating very high predictive power. This study contributes as the first empirical evidence from the Eastern Indonesian context that integrates Social Cognitive Theory and Social Exchange Theory and extends the cross-context validity of both theories beyond Western countries. It also produces a psychological mediation model that has not been tested in the hospitality HR management literature. These findings provide a basis for hotel managers to design HR development programs based on strengthening employee self-efficacy and emotional engagement, as well as for tourism industry policymakers in Southwest Papua to prioritize HR certification that integrates psychological capacity in response to the pressures of sustainable tourism growth.